К вопросу о речевой агрессии и инвективах в современных антилиберальных новых медиа - Kravcova , Liudmila (Verbum, 2019)
The article explores the use of verbal aggression by anti-liberal “new media”. This source material was selected following the infamous Financial Times interview with Vladimir Putin, where he proclaimed that liberalism had become obsolete. The study explores the purpose, objects, and means of expressing verbal aggression. This study highlights the main ways in which a holistic trend of political philosophy comes under a sustained attack.The research establishes that lexemes without a default negative connotation, rather than pejorative invectives, are the primary means of expressing aggression. The study further maintains the existence of certain verbal aggression discourse algorithm whereby the use of one potentially aggressive lexeme automatically triggers the use of another lexeme. The analysis shows that anti-liberal discourse is intertwined with antisemitism, homophobia, and negative sentiment towards the internet.Anti-liberal environment is not limited to pro-government sentiment – occasionally the head of state alsocomes under its critique and its standard allegations. The source of verbal aggression is particularly crucial in the “new media” era: verbal aggression can originate both in governmental institutions and the demassified field. The origin of verbal aggression will further determine its consequences, ranging from impacting the fate of the object of verbal aggression to uniting the supporters sharing the sentiment behind the verbal aggression and/or pro-government opinion. Here neutral lexemes without a default negative connotation take on the function of the means of verbal aggression. This way neutral words such as liberal, Jew, gay become pejorative invectives. These words now carry a high potential for expressing aggression when used in conjunction with other words and phrases.
Keywords: когнитивная лингвистика; инвективы; либерализм; антилиберализм; демассификация; новые медиа